Nanodiamond based supermolecular nanocomposites: preparation and biocompatibility evaluation. Issue 117 (11th November 2015) - Liu, Meiying; Xu, Dazhuang; Wang, Ke; Deng, Fengjie; Wan, Qing; Zeng, Guangjian; Huang, Qiang; Zhang, Xiaoyong; Wei, Yen
Abstract : We reported for the first time that water dispersible and biocompatible ND based supermolecular nanocomposites can be facilely and efficiently fabricated via host–guest interactions. Abstract : Nanodiamond (ND) is a relative novel carbon nanomaterial that has recently received great research attention for biomedical applications thanks to its small size, unique luminescent properties and good biocompatibility. However, the water dispersibility of such a material has significantly impacted its performance. Although considerable advance has been made for the surface modification of ND, facile and efficient strategies are still highly desirable to be developed. In this study, high water dispersible ND based nanocomposites have been fabricated for the first time through host–guest interactions between adamantane and β-cyclodextrin (β-CD). Adamantane chloride was first reacted with the hydroxyl group of ND through esterification to obtain ND-Ad. Then β-CD was orthogonally immobilized onto ND-Ad through a host–guest interaction. These reactions can occur within 30 min under rather mild experimental conditions, including room temperature, air atmosphere, absence of hazardous reagents and expensive equipments. The successful preparation of such ND based supermolecular nanocomposites (ND-Ad/β-CD) was confirmed by a number of characterization techniques. ND-Ad/β-CD showed good water dispersibility and excellent cytocompatibility, making it promising for biomedical applications.